The Effectiveness of Implementation of Online Lectures on Student Satisfaction in Higher Education Institutions (Case Study of the President University) - Yeni Fajrin; Adhi Setyo Santoso (Sekolah Tinggi Manajemen IPMI, 2021)
This study aims to identify and obtain information about the effectiveness of the implementation of online lectures during the COVID-19 pandemic at Higher Education Institutions, especially President University. Data was collected by looking at the results of student satisfaction assessments of lecturers during the teaching and learning process, namely in the PUIS (President University Information System) system in the